E-PROLIC sebagai Upaya Mengatasi Kesenjangan Kebutuhan Tenaga Perawat - Debat Sendy Asmoro; Siti Zuhriyah; Atik Setiawan W; Moch. Gandung Satriya (Yayasan Inspirasi El Burhani, 2026)
Introduction: High-quality nursing services are critical to hospital performance; however, they are frequently constrained by imbalances between nurse availability, competency, and workload. Simpang Lima Gumul Kediri Regional Hospital experiences such challenges, as indicated by excessive workload conditions in the Gelatik Ward and potential fatigue risks in the Perkutut Ward. Additionally, administrative issues arise from nurses’ limited awareness of the validity periods of their Work Plan Requirements (RKK) and Practice Permits (SIP), which can lead to temporary deactivation from clinical duties and reassignment to non-clinical tasks, thereby reducing effective nursing capacity. Objective: This community service program aims to develop and implement a digital system to support nursing workforce management by addressing staffing workload gaps and improving administrative compliance related to RKK and SIP validity. Methods: The program employed the introduction and implementation of E-PROLIC (Electronic Professional License), a digital platform designed to monitor the validity status of nurses’ RKK and SIP. The system integrates administrative tracking with workload analysis using the Workload Indicator of Staffing Need (WISN) method to support staffing planning and prevent permit expiration. Results: The WISN analysis showed that the Gelatik Ward requires 20.21 nurses but has only 12 available, resulting in a WISN Ratio of 0.59, which indicates an excessive workload. In contrast, the Perkutut Ward requires 12.78 nurses and has 13 available, yielding a WISN Ratio of 1.00, indicating adequate staffing levels. Conclusion: The implementation of E-PROLIC provides a digital mechanism for monitoring RKK and SIP validity while supporting workload-based staffing analysis, thereby contributing to improved administrative management and nursing workforce planning.